Effect of “Xuling DingJin” in Tai Chi on Lumbar Spine Biomechanics during Walking - Duan, Yiting; Liu, Haibin; Liu, Liqing; Wang, Ziyang; Gao, Fan; Li, Suheng; Yang, Yulong; Yang, Shuye; Yan, Shudong (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2025)
Background: Low back pain is a common condition. The Tai Chi posture of “Xuling Dingjin” may help alleviate lower back pain, but its biomechanical characteristics are not yet fully understood. This study aims to explore the effects of the “Xuling Dingjin” posture on the biomechanics of the lumbar spine during walking, and verify its potential benefits for its application in injury prevention and rehabilitation. Methods: 12 experienced Tai Chi practitioners participated in the study. The VICON motion capture system, AMTI force measurement platform, and OpenSim software were used to collect lumbar biomechanical data, including activation of the paravertebral muscles and the bending angles of the L4-L5 segment of the lumbar spine. Results: Walking with “Xuling Dingjin” posture significantly increased the activation levels of all target muscles (P <0.05), especially the deep stabilizing muscles (multifidus and longissimus). The forward flexion angle of the L4-L5 segment in the sagittal plane decreased and the trend of asymmetric lateral flexion in the coronal plane was corrected, while there was no significant difference in the bending angle in the horizontal plane. Conclusion: Maintaining the “Xuling Dingjin” posture during walking may enhances the dynamic stability of the spine and reduces the risk of unilateral overload.
Keywords: Tai Chi; Walking; Lumbar; Biomechanics; Opensim; Muscle activation; Balance control; Xuling Dingjing